2017
DOI: 10.1016/j.jhsa.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Patient-Reported Outcomes Measurement Information System (PROMIS) Upper Extremity (UE) Versus Physical Function (PF) Computer Adaptive Tests (CATs) in Upper Extremity Clinics

Abstract: Purpose To examine the performance of the PROMIS Upper Extremity Function CAT relative to the PROMIS Physical Function CAT in patients seeking specialty care for upper extremity conditions. Methods This observational trial analyzed prospectively collected PROMIS Upper Extremity and Physical Function CAT scores from 5202 adult patients with 10344 outpatient clinic visits presenting to a tertiary orthopaedic clinic. Pearson’s correlation coefficient was utilized to evaluate the association between initial Phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…The more recently developed PROMIS UE CAT, which was designed to specifically assess UE function, may have increased sensitivity to capture UE impairment. However, similar to the UE TESS, the PROMIS UE CAT has demonstrated a ceiling effect [7], [8].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The more recently developed PROMIS UE CAT, which was designed to specifically assess UE function, may have increased sensitivity to capture UE impairment. However, similar to the UE TESS, the PROMIS UE CAT has demonstrated a ceiling effect [7], [8].…”
Section: Discussionmentioning
confidence: 90%
“…CAT is completed when the consistency of the answers is sufficient for scoring. PROMIS CAT has been studied in several orthopaedic populations [20], specifically including hand and shoulder [1], [2], [8], [13], [24], [25], [32], foot and ankle [18], sports [16], [28], adult reconstruction [20], spine [30] and trauma [19], [18], [21], [33], [29], [1], [2], [8], [13], [16], [20], [25], [31], as well as various oncologic subspecialities [15], [34], [5], [9]. There is currently a widespread initiative for adoption and inclusion of PROMIS domains in all Federal Drug Administration–funded and industry-funded clinical oncology outcome research.…”
Section: Introductionmentioning
confidence: 99%
“…In a subgroup aged 21 years or younger, ceiling effects were 71.1% at 6 months and 81% at 2 years. Ceiling effects were found for 3% of patients (T score of 56 or higher) undergoing arthroscopic rotator cuff repair (285) and 7.2% (T score of 56 or higher) of patients with hand or shoulder conditions (286). The latter study also reported 1.2% floor effects.…”
Section: Promis Physical Function Upper Extremity Catmentioning
confidence: 99%
“…PROMIS PF Short Form 8a: r = 0.73 to 0.77 in upper extremity trauma (289). PROMIS PF CAT: r = 0.63 in shoulder instability (287), r = 0.70 in rotator cuff pathology (282), r = 0.69 (baseline) and r = 0.53 (change) in upper extremity conditions (286), and r = 0.48 in hand and upper extremity conditions (276). PROMIS Pain Interference CAT: r = −0.60 in hand and upper extremity conditions (276).…”
Section: Promis Physical Function Upper Extremity Catmentioning
confidence: 99%
“…25 The PROMIS UE shows a strong correlation with the PROMIS PF and a similar ceiling effect (7%) in an orthopedic sample, though patients with elbow conditions evidenced lower scores on the PROMIS UE than for patients with hand conditions. 3 Until this work is completed on PROMIS refinements, the DASH may be selected as a better fit for assessing elbow orthopedic outcomes in high functioning patients.…”
Section: Discussionmentioning
confidence: 99%